The semantics of deductive databases - Ross, Kenneth A. 1936- (1991)
Abstract: "The major advantage of a deductive database is the ability to write queries and programs declaratively, using both facts and simple logical rules to represent knowledge. Declarativeness makes queries easier to write, and thus reduces the time taken and the programming skills needed to specify a query. Two important questions arise: What should the semantics of such a deductive database language be, and how should declarative queries be answered efficiently? We address both of these questions. The question of semantics becomes complicated when one needs some sort of negation by default. For example, the absence of a fact stating that a student is in a class should allow us to conclude that the student is not in that class
Stanford, Calif., Univ., Diss.
Keywords: Deductive databases; Semantik; Deduktives Datenbanksystem; Hochschulschrift